Porous sound-absorbing brick for low-frequency noise and preparation method of porous sound-absorbing brick

By using coal gangue and other materials to prepare porous sound-absorbing bricks, the problem of poor performance in low-frequency noise control in traditional acoustic barrier materials is solved, the effect of efficient absorption of low-frequency noise is achieved, and the resource utilization and environmental protection of waste is promoted.

CN119874406APending Publication Date: 2025-04-25GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510102493.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing acoustic barrier materials are not effective in low-frequency noise control, and it is difficult to effectively absorb low-frequency noise such as traffic noise.

Method used

Porous sound-absorbing bricks are prepared by using materials such as coal gangue, clay, glass powder, expanded perlite and plant foaming agents to achieve the interconnected distribution of internal pores and improve the absorption capacity of low-frequency noise.

Benefits of technology

It significantly improves the absorption capacity of porous sound-absorbing bricks to low-frequency noise, enhances acoustic performance and durability, and realizes resource conversion and environmental protection of industrial waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874406A_ABST
    Figure CN119874406A_ABST
Patent Text Reader

Abstract

The invention discloses a porous sound absorption brick for low-frequency noise and a preparation method thereof, and relates to the technical field of building material preparation. The porous sound-absorbing brick comprises the following components in parts by weight: 10-55 parts of coal gangue, 35-80 parts of clay, 4-6 parts of glass powder, 2-4 parts of expanded perlite and 1-3 parts of a plant foaming agent. The preparation method comprises the following steps: crushing and grinding coal gangue and clay to obtain coal gangue powder; adding the clay, the glass powder, the expanded perlite and the water into the coal gangue powder, stirring, adding the plant foaming agent, stirring, pouring the obtained mixed material into a mold, drying, demolding, firing at high temperature, and cooling to obtain the porous sound-absorbing brick for low-frequency noise. According to the porous sound absorption brick for low-frequency noise prepared by the method provided by the invention, communicated distribution of internal pores is realized, the low-frequency noise absorption capacity is remarkably improved, and the problem that a traditional sound barrier material is poor in low-frequency noise control effect is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material preparation, and in particular to a porous sound-absorbing brick for low-frequency noise and a preparation method thereof. Background Art

[0002] At present, sound barrier sound-absorbing materials perform well in controlling high-frequency noise, but their sound absorption effect is often unsatisfactory when facing low-frequency noise, such as traffic noise. Since low-frequency noise has a long wavelength and can easily penetrate traditional sound barrier materials, the noise reduction effect is limited, which brings challenges to the protection of urban sound environment.

[0003] Gangue is solid waste generated during coal mining and washing. It has long been regarded as a burden. Large amounts of gangue not only occupy land, but also cause serious environmental pollution. If abandoned, it will occupy a large area of ​​land. The sulfide in the gangue will escape or leach into the air, farmland and water bodies. Gangue heaps will also spontaneously combust and cause fires, or collapse in the rainy season, silting up rivers and causing disasters.

[0004] At present, there is no related report on using coal gangue to prepare sound-absorbing materials for absorbing low-frequency noise. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a porous sound-absorbing brick for low-frequency noise and a preparation method thereof. The porous sound-absorbing brick prepared by the method provided by the present invention realizes a connected distribution of internal pores, significantly improves the absorption capacity of low-frequency noise, and effectively solves the problem that traditional sound barrier materials are not effective in controlling low-frequency noise.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention to solve its technical problem is: to provide a porous sound-absorbing brick for low-frequency noise, comprising the following components by weight: 10-55 parts of coal gangue, 35-80 parts of clay, 4-6 parts of glass powder, 2-4 parts of expanded perlite and 1-3 parts of plant foaming agent.

[0007] Furthermore, the porous sound-absorbing bricks for low-frequency noise include the following components in parts by weight: 30 parts of coal gangue, 60 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0008] Furthermore, the density of coal gangue is 1.7-1.9 g / cm 3 , particle size is 0.24-0.26mm.

[0009] Furthermore, the density of coal gangue is 1.8 g / cm 3 , particle size is 0.25mm.

[0010] Furthermore, the clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64-65:13-14:10-11:2-3:1-2:2-3:3-4.

[0011] Furthermore, the clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64.6:13.9:10.2:2.1:1.6:2.9:3.5.

[0012] Further, the glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72-73:11-12:3-4:3-4:1-2:0.9-1:0.2-0.3.

[0013] Further, the glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72.68:11.41:3.41:3.41:1.05:0.98:0.25.

[0014] The beneficial effect of adopting the above further solution is that the glass powder has the characteristics of high melting point and high hardness, which forms a strong skeleton in the brick body and effectively improves the overall strength of the brick body.

[0015] Further, the expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69-70:13-14:8-9:3-4:2-3:0.9-1:0.5-0.6.

[0016] Further, the expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69.3:13.3:8.3:3.7:2.9:0.93:0.51.

[0017] Further, the particle size of the expanded perlite is 6.4-6.6 mm, and the effective water content is 44-45%.

[0018] Furthermore, the particle size of the expanded perlite is 6.5 mm, and the effective water content is 45%.

[0019] Furthermore, the weight of expanded perlite in a water-saturated state is 450-600 kg per cubic meter.

[0020] Furthermore, the plant foaming agent comprises the following components in parts by weight: 2-5 parts of rosin extract, 10-20 parts of wheat bran, 10-20 parts of corn bran, 15-25 parts of molasses and 40-55 parts of defatted soybean meal.

[0021] Furthermore, the plant foaming agent includes the following components in parts by weight: 3 parts of rosin extract, 15 parts of wheat bran, 15 parts of corn bran, 20 parts of molasses and 50 parts of defatted soybean meal.

[0022] The beneficial effect of adopting the above further scheme is: using a plant-based foaming agent, the surface-activated active molecules are orderly distributed in the bubble liquid, the foam has good viscosity and repair ability, and the foam stabilizing effect is good.

[0023] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0024] S1. crushing the gangue and clay respectively, grinding and classifying the crushed gangue to obtain gangue powder with uniform particle size;

[0025] S2, adding clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stirring until fully mixed, then adding a plant foaming agent, stirring again to foam, and obtaining a mixed material;

[0026] S3, pouring the mixed material obtained in step S2 into a mold, letting it stand, drying and demoulding, and then firing it at high temperature. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0027] The beneficial effect of adopting the above further scheme is that after the clay comes into contact with water, its physical properties are revealed and it has significant plasticity.

[0028] Further, in step S1, the particles are broken into small pieces.

[0029] Furthermore, in step S1, grinding is performed using screening equipment.

[0030] Furthermore, in step S1, the particle size of the coal gangue powder is 50-70 mesh.

[0031] Furthermore, in step S2, the amount of water added is 8-15% of the mass of the mixed material.

[0032] Furthermore, in step S2, stirring is performed at 1100-1300 r / min for 4-6 min until fully mixed, and then stirring is performed at 700-900 r / min for 2-4 min.

[0033] Furthermore, in step S2, stirring is performed at 1200 r / min for 5 min until the mixture is fully mixed, and then stirring is performed at 800 r / min for 3 min.

[0034] Further, in step S3, the specification of the mold is Φ950-970mm×240-260mm.

[0035] Further, in step S3, the specification of the mold is Φ960mm×250mm.

[0036] Further, in step S3, the mixture is poured into a mold and allowed to stand for 24-48 hours, and then dried at 30-40° C. for 24-48 hours.

[0037] Further, in step S3, the product is placed in a drying oven for drying.

[0038] A further beneficial approach to the above is to avoid cracking due to excessive temperature.

[0039] Further, in step S3, the steel is fired at a high temperature of 900-1000° C. for 2.5-3.5 hours.

[0040] Further, in step S3, the product is fired at a high temperature of 900-1000° C. for 3 hours.

[0041] In summary, the present invention has the following beneficial effects:

[0042] 1. The present invention uses coal gangue to prepare porous sound-absorbing bricks. By regulating the sintering process, the efficient conversion of coal gangue is achieved, and the porous structure is precisely controlled to achieve the interconnected distribution of internal pores, which significantly improves the absorption capacity of low-frequency noise and enhances the acoustic performance and durability of porous sound-absorbing bricks. During the sintering process of porous sound-absorbing bricks, the coal gangue bricks make full use of the heat energy contained in the coal gangue itself, effectively reducing the consumption of clay and coal, and realizing the transformation of industrial waste into resources. The present invention also uses plant foaming agents to prepare absorbent materials with interconnected internal pores, significantly increasing the interconnected pores inside the material, thereby improving the sound absorption performance of the material for low-frequency noise. Glass powder is used to form a solid skeleton in the fired brick body, which effectively improves the overall strength of the brick body, increases the density and hardness of the brick body, and improves the compressive strength and wear resistance of the brick body. The use of expanded pearls can greatly reduce the weight of the bricks, making them easier to transport and install. At the same time, expanded perlite can also optimize the internal structure of the bricks, increase the porosity, and further enhance their sound absorption effect on low-frequency noise, making porous sound-absorbing bricks more widely used in the field of noise control. Finally, clay, as the basic supporting material, ensures that the bricks have good plasticity, adhesion and fire resistance, laying a solid foundation for the widespread application of porous sound-absorbing bricks in the field of noise control. The synergistic gain effect of each substance provides new ideas and directions for the development of low-frequency noise control technology, which has important practical value and social significance.

[0043] 2. Aiming at the shortcomings of existing low-frequency traffic noise absorption technology, the present invention uses environmentally friendly materials such as plant foaming agents, glass powder, expanded perlite and clay to prepare high-efficiency porous sound-absorbing bricks. The porous sound-absorbing bricks effectively solve the shortcomings of traditional sound barrier materials in low-frequency noise control. At the same time, the porous sound-absorbing bricks also have the advantages of high strength, light weight, easy transportation and installation, further optimize the noise control effect, and broaden the scope of application. The present invention not only helps to improve the quality of urban sound environment, solves the environmental problems caused by coal gangue accumulation, realizes the effective recycling of resources, but also reduces the cost of raw materials for the production of building materials, and has significant economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The sound absorption coefficient of the porous sound-absorbing brick for low-frequency noise prepared in Example 1 at different frequencies;

[0045] Figure 2 The sound absorption coefficient of the porous sound-absorbing brick for low-frequency noise prepared in Example 2 at different frequencies;

[0046] Figure 3 The sound absorption coefficient of the porous sound-absorbing brick for low-frequency noise prepared in Example 3 at different frequencies;

[0047] Figure 4 The sound absorption coefficient of the porous sound-absorbing brick for low-frequency noise prepared in Example 4 at different frequencies;

[0048] Figure 5 The sound absorption coefficients of the porous sound-absorbing bricks for low-frequency noise prepared in Example 5 at different frequencies. DETAILED DESCRIPTION

[0049] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0050] Example 1

[0051] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 30 parts of coal gangue, 60 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0052] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64.6:13.9:10.2:2.1:1.6:2.9:3.5.

[0053] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72.68:11.41:3.41:3.41:1.05:0.98:0.25.

[0054] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69.3:13.3:8.3:3.7:2.9:0.93:0.51.

[0055] The plant foaming agent comprises the following components in parts by weight: 3 parts of rosin extract, 15 parts of wheat bran, 15 parts of corn bran, 20 parts of molasses and 50 parts of defatted soybean meal.

[0056] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0057] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.8 g / cm 3 , particle size is 0.25mm;

[0058] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1200 r / min for 5 min until fully mixed, then add a plant foaming agent, and stir at 800 r / min for 3 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.5 mm, the effective water content is 45%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 10% of the mass of the mixed material;

[0059] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 960 mm × 250 mm, let it stand for 36 hours, dry it at 35°C for 36 hours, demould it, and then sinter it at a high temperature of 900-1000°C for 3 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0060] Example 2

[0061] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 40 parts of coal gangue, 50 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0062] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64.6:13.9:10.2:2.1:1.6:2.9:3.5.

[0063] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72.68:11.41:3.41:3.41:1.05:0.98:0.25.

[0064] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69.3:13.3:8.3:3.7:2.9:0.93:0.51.

[0065] The plant foaming agent comprises the following components in parts by weight: 3 parts of rosin extract, 15 parts of wheat bran, 15 parts of corn bran, 20 parts of molasses and 50 parts of defatted soybean meal.

[0066] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0067] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.8 g / cm 3 , particle size is 0.25mm;

[0068] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1200 r / min for 5 min until fully mixed, then add a plant foaming agent, and stir at 800 r / min for 3 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.5 mm, the effective water content is 45%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 10% of the mass of the mixed material;

[0069] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 960 mm × 250 mm, let it stand for 36 hours, dry it at 35°C for 36 hours, demould it, and then sinter it at a high temperature of 900-1000°C for 3 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0070] Example 3

[0071] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 50 parts of coal gangue, 40 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0072] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64.6:13.9:10.2:2.1:1.6:2.9:3.5.

[0073] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72.68:11.41:3.41:3.41:1.05:0.98:0.25.

[0074] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69.3:13.3:8.3:3.7:2.9:0.93:0.51.

[0075] The plant foaming agent comprises the following components in parts by weight: 3 parts of rosin extract, 15 parts of wheat bran, 15 parts of corn bran, 20 parts of molasses and 50 parts of defatted soybean meal.

[0076] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0077] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.8 g / cm 3 , particle size is 0.25mm;

[0078] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1200 r / min for 5 min until fully mixed, then add a plant foaming agent, and stir at 800 r / min for 3 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.5 mm, the effective water content is 45%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 10% of the mass of the mixed material;

[0079] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 960 mm × 250 mm, let it stand for 36 hours, dry it at 35°C for 36 hours, demould it, and then sinter it at a high temperature of 900-1000°C for 3 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0080] Example 4

[0081] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 55 parts of coal gangue, 35 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0082] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64.6:13.9:10.2:2.1:1.6:2.9:3.5.

[0083] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72.68:11.41:3.41:3.41:1.05:0.98:0.25.

[0084] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69.3:13.3:8.3:3.7:2.9:0.93:0.51.

[0085] The plant foaming agent comprises the following components in parts by weight: 3 parts of rosin extract, 15 parts of wheat bran, 15 parts of corn bran, 20 parts of molasses and 50 parts of defatted soybean meal.

[0086] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0087] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.8 g / cm 3 , particle size is 0.25mm;

[0088] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1200 r / min for 5 min until fully mixed, then add a plant foaming agent, and stir at 800 r / min for 3 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.5 mm, the effective water content is 45%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 10% of the mass of the mixed material;

[0089] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 960 mm × 250 mm, let it stand for 36 hours, dry it at 35°C for 36 hours, demould it, and then sinter it at a high temperature of 900-1000°C for 3 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0090] Example 5

[0091] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 10 parts of coal gangue, 80 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0092] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64.6:13.9:10.2:2.1:1.6:2.9:3.5.

[0093] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72.68:11.41:3.41:3.41:1.05:0.98:0.25.

[0094] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69.3:13.3:8.3:3.7:2.9:0.93:0.51.

[0095] The plant foaming agent comprises the following components in parts by weight: 3 parts of rosin extract, 15 parts of wheat bran, 15 parts of corn bran, 20 parts of molasses and 50 parts of defatted soybean meal.

[0096] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0097] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.8 g / cm 3 , particle size is 0.25mm;

[0098] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1200 r / min for 5 min until fully mixed, then add a plant foaming agent, and stir at 800 r / min for 3 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.5 mm, the effective water content is 45%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 10% of the mass of the mixed material;

[0099] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 960 mm × 250 mm, let it stand for 36 hours, dry it at 35°C for 36 hours, demould it, and then sinter it at a high temperature of 900-1000°C for 3 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0100] Example 6

[0101] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 10 parts of coal gangue, 35 parts of clay, 4 parts of glass powder, 2 parts of expanded perlite and 1 part of a plant foaming agent.

[0102] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64:13:10:2:1:2:3.

[0103] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72:11:3:3:1:0.9:0.2.

[0104] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69:13:8:3:2:0.9:0.5.

[0105] The plant foaming agent comprises the following components in parts by weight: 2 parts of rosin extract, 10 parts of wheat bran, 10 parts of corn bran, 15 parts of molasses and 40 parts of defatted soybean meal.

[0106] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0107] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.7 g / cm 3 , particle size is 0.24mm;

[0108] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1100 r / min for 4 min until fully mixed, then add a plant foaming agent, and stir at 700 r / min for 2 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.4 mm, the effective water content is 44%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 8% of the mass of the mixed material;

[0109] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 950 mm × 240 mm, let it stand for 24 hours, dry it at 30°C for 24 hours, demould it, and then burn it at a high temperature of 900-1000°C for 2.5 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0110] Example 7

[0111] A porous sound-absorbing brick for low-frequency noise comprises the following components in parts by weight: 55 parts of coal gangue, 80 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

[0112] The above-mentioned clay includes the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 65:14:11:3:2:3:4.

[0113] The glass powder includes the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 73:12:4:4:2:1:0.3.

[0114] The expanded perlite includes the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 70:14:9:4:3:1:0.6.

[0115] The plant foaming agent comprises the following components in parts by weight: 5 parts of rosin extract, 20 parts of wheat bran, 20 parts of corn bran, 25 parts of molasses and 55 parts of defatted soybean meal.

[0116] The method for preparing the porous sound-absorbing brick for low-frequency noise comprises the following steps:

[0117] S1. Crush the gangue and clay separately, grind and grade the crushed gangue using screening equipment to obtain gangue powder with uniform particle size. The density of the gangue is 1.9 g / cm 3 , particle size is 0.26mm;

[0118] S2. Add clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stir at 1300 r / min for 6 min until fully mixed, then add a plant foaming agent, and stir at 900 r / min for 4 min to foam it to obtain a mixed material. The particle size of the expanded perlite is 6.6 mm, the effective water content is 45%, the weight per cubic meter in the saturated state is 450-600 kg, and the amount of water added is 15% of the mass of the mixed material;

[0119] S3. Pour the mixed material obtained in step S2 into a mold with a specification of 970 mm × 260 mm, let it stand for 48 hours, dry it at 40°C for 48 hours, demould it, and then sinter it at a high temperature of 900-1000°C for 3.5 hours. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

[0120] Comparative Example 1

[0121] A sound-absorbing brick, compared with Example 1, is different in that Comparative Example 1 does not contain coal gangue.

[0122] Comparative Example 2

[0123] A sound-absorbing brick, compared with Example 1, is different in that Comparative Example 2 does not contain clay.

[0124] Comparative Example 3

[0125] A sound-absorbing brick, compared with Example 1, is different in that Comparative Example 3 does not contain glass powder.

[0126] Comparative Example 4

[0127] A sound-absorbing brick, compared with Example 1, is different in that Comparative Example 4 does not contain expanded perlite.

[0128] Comparative Example 5

[0129] A sound-absorbing brick, compared with Example 1, is different in that Comparative Example 5 does not contain a plant foaming agent.

[0130] Test Example 1

[0131] The compressive strength, porosity and pH value of the porous sound-absorbing bricks for low-frequency noise prepared in Examples 1-5 and the sound-absorbing bricks prepared in Comparative Examples 1-5 were tested, and the results are shown in Table 1.

[0132] Table 1 Performance test results

[0133] Group Compressive strength(MPa) Porosity (%) pH Example 1 12 75.6 8.63 Example 2 11.8 77.8 8.61 Example 3 10.5 78.9 8.72 Example 4 12.4 80.1 8.76 Example 5 12.4 70.9 8.28 Comparative Example 1 9.5 51.2 7.23 Comparative Example 2 9.8 62.7 7.14 Comparative Example 3 8.7 63.5 7.45 Comparative Example 4 8.5 55.4 7.27 Comparative Example 5 9.2 30.8 7.19

[0134] It can be seen from Table 1 that the various performances of the porous sound-absorbing bricks for low-frequency noise provided by the present invention are significantly higher than those of the sound-absorbing bricks provided in the comparative example. This is because the compressive strength of the sound-absorbing bricks provided in the comparative example is relatively low, and the porosity range is large and not necessarily optimal, while the porous sound-absorbing bricks for low-frequency noise provided in the embodiments show more excellent performance in terms of compressive strength, porosity, etc.

[0135] Test Example 2

[0136] The sound absorption coefficients of the porous sound-absorbing bricks for low-frequency noise prepared in Examples 1-5 were tested at different frequencies. The results were as follows: Figure 1-Figure 5 shown.

[0137] Depend on Figure 1 It can be seen that the porous sound-absorbing bricks prepared in Example 1 for low-frequency noise have a better sound absorption coefficient effect in the low-frequency range of 400-800Hz.

[0138] Depend on Figure 2 It can be seen that the porous sound-absorbing bricks prepared in Example 2 for low-frequency noise have a better sound absorption coefficient effect in the low-frequency range of 400-800Hz.

[0139] Depend on Figure 3 It can be seen that the porous sound-absorbing bricks for low-frequency noise prepared in Example 3 have a better sound absorption coefficient effect in the low-frequency range of 500-1300 Hz.

[0140] Depend on Figure 4 It can be seen that the porous sound-absorbing bricks prepared in Example 4 for low-frequency noise have a better sound absorption coefficient effect in the low-frequency range of 500-1000 Hz.

[0141] Depend on Figure 5 It can be seen that the porous sound-absorbing bricks for low-frequency noise prepared in Example 5 have a better sound absorption coefficient effect in the low-frequency range of 500-1000Hz.

[0142] In summary, the porous sound-absorbing bricks for low-frequency noise prepared by the present invention significantly improve the absorption capacity of low-frequency noise.

[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A porous sound-absorbing brick for low-frequency noise, characterized in that: The invention comprises the following components in parts by weight: 10-55 parts of coal gangue, 35-80 parts of clay, 4-6 parts of glass powder, 2-4 parts of expanded perlite and 1-3 parts of plant foaming agent.

2. The porous sound-absorbing brick for low-frequency noise according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 30 parts of coal gangue, 60 parts of clay, 5 parts of glass powder, 3 parts of expanded perlite and 2 parts of plant foaming agent.

3. The porous sound-absorbing brick for low-frequency noise according to claim 1 or 2, characterized in that: The density of the coal gangue is 1.7-1.9 g / cm 3 , particle size is 0.24-0.26mm; The expanded perlite has a particle size of 6.4-6.6 mm and an effective moisture content of 44-45%; The plant foaming agent comprises the following components in parts by weight: 2-5 parts of rosin extract, 10-20 parts of wheat bran, 10-20 parts of corn bran, 15-25 parts of molasses and 40-55 parts of defatted soybean meal.

4. The porous sound-absorbing brick for low-frequency noise according to claim 1 or 2, characterized in that: The clay comprises the following elements: silicon, aluminum, iron, calcium, titanium, potassium and magnesium, and the mass ratio of silicon, aluminum, iron, calcium, titanium, potassium and magnesium is 64-65:13-14:10-11:2-3:1-2:2-3:3-4.

5. The porous sound-absorbing brick for low-frequency noise according to claim 1 or 2, characterized in that: The glass powder comprises the following elements: silicon, aluminum, calcium, potassium, magnesium, iron and titanium, and the mass ratio of silicon, aluminum, calcium, potassium, magnesium, iron and titanium is 72-73:11-12:3-4:3-4:1-2:0.9-1:0.2-0.

3.

6. The porous sound-absorbing brick for low-frequency noise according to claim 1 or 2, characterized in that: The expanded perlite comprises the following elements: silicon, aluminum, potassium, calcium, iron, magnesium and barium, and the mass ratio of silicon, aluminum, potassium, calcium, iron, magnesium and barium is 69-70:13-14:8-9:3-4:2-3:0.9-1:0.5-0.

6.

7. The method for preparing the porous sound-absorbing brick for low-frequency noise according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. crushing the gangue and clay respectively, grinding and classifying the crushed gangue to obtain gangue powder with uniform particle size; S2, adding clay, glass powder, expanded perlite and water to the gangue powder obtained in step S1, stirring until fully mixed, then adding a plant foaming agent, stirring again to foam, and obtaining a mixed material; S3, pouring the mixed material obtained in step S2 into a mold, letting it stand, drying and demoulding, and then firing it at high temperature. After cooling, a porous sound-absorbing brick for low-frequency noise is obtained.

8. The method for preparing a porous sound-absorbing brick for low-frequency noise according to claim 7, characterized in that: In step S2, stirring is performed at 1100-1300 r / min for 4-6 min until the mixture is fully mixed, and then stirring is performed at 700-900 r / min for 2-4 min.

9. The method for preparing a porous sound-absorbing brick for low-frequency noise according to claim 7, characterized in that: In step S3, the mixture is poured into a mold and allowed to stand for 24-48 hours, and then dried at 30-40° C. for 24-48 hours.

10. The method for preparing a porous sound-absorbing brick for low-frequency noise according to claim 7, characterized in that: In step S3, the steel is fired at a high temperature of 900-1000° C. for 2.5-3.5 hours.